Preventive effect of insect tea primary leaf (Malus sieboldii (Regal) Rehd.) extract on D‐galactose‐induced oxidative damage in mice - Yi, Ruokun (Food Sci Nutr, 2020)
Insect tea is consumed as a health beverage in China. The insect tea primary leaf (ITPL) is rich in bioactive substances, which are also used as traditional Chinese medicine. This study investigated the role of ITPL in reducing the oxidative response induced by D‐galactose in mice. Mice were intraperitoneally injected with D‐galactose to induce oxidative damage. The effect of ITPL was tested by pathological observation, serum detection with kits, quantitative polymerase chain reaction, and Western blot. The experimental results show that ITPL increased the thymus, brain, heart, liver, spleen, and kidney indices of oxidized mice. ITPL increased superoxide dismutase, glutathione peroxidase, and glutathione levels and reduced nitric oxide and malondialdehyde levels in the serum, liver, and spleen in oxidative damaged mice. The pathological observations show that ITPL reduced the oxidative damage of the liver and spleen in mice induced with D‐galactose. Simultaneously, ITPL upregulated mRNA expression of neuronal nitric oxide synthase, endothelial nitric oxide synthase, cuprozinc‐superoxide dismutase, manganese superoxide dismutase, catalase, heme oxygenase‐1, nuclear factor‐erythroid 2 related factor 2, γ‐glutamylcysteine synthetase, and NAD(P)H dehydrogenase [quinone] 1, and downregulated the expression of inducible nitric oxide synthase in the liver and spleen of oxidized mice. ITPL had beneficial preventive effects on the oxidative damage caused by D‐galactose in mice and was more effective as an antioxidant than vitamin C. The component analysis test by high‐performance liquid chromatography indicated that ITPL contained the following seven compounds: neochlorogenic acid, cryptochlorogenic acid, rutin, kaempferin, isochlorogenic acid B, isochlorogenic acid A, and hesperidin. ITPL is a plant with excellent antioxidant activities derived from its bioactive substances.